2016
DOI: 10.1371/journal.ppat.1005672
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Host-Pathogen Interaction through sRNA in Bacterial Outer Membrane Vesicles

Abstract: Bacterial outer membrane vesicle (OMV)-mediated delivery of proteins to host cells is an important mechanism of host-pathogen communication. Emerging evidence suggests that OMVs contain differentially packaged short RNAs (sRNAs) with the potential to target host mRNA function and/or stability. In this study, we used RNA-Seq to characterize differentially packaged sRNAs in Pseudomonas aeruginosa OMVs, and to show transfer of OMV sRNAs to human airway cells. We selected one sRNA for further study based on its st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
436
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(447 citation statements)
references
References 65 publications
10
436
1
Order By: Relevance
“…There is precedent for small RNAs that are used by microorganisms to communicate across kingdoms with their hosts between fungi and plants18, intestinal nematodes and their mammalian hosts46, bacteria and humans21, and even in the reverse direction between sickle cell red blood cells and malaria parasites47. As a result, we explored whether the small RNAs found in MalaEx may also map to the human genome and represent cross-kingdom communication, possibly to modulate host immune response or to increase nutrient availability or to compete with other microbes on the ecological niche of human skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is precedent for small RNAs that are used by microorganisms to communicate across kingdoms with their hosts between fungi and plants18, intestinal nematodes and their mammalian hosts46, bacteria and humans21, and even in the reverse direction between sickle cell red blood cells and malaria parasites47. As a result, we explored whether the small RNAs found in MalaEx may also map to the human genome and represent cross-kingdom communication, possibly to modulate host immune response or to increase nutrient availability or to compete with other microbes on the ecological niche of human skin.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, B. cinerea , an aggressive fungal pathogen that is able to infect more than 200 plant species, uses small RNAs to interfere with the host RNA interference (RNAi) machinery and selectively silences host immunity genes to achieve infection18. Furthermore, it was recently demonstrated that Pseudomonas aeruginosa is able to reduce the host immune response by releasing EVs containing small RNA that inhibit the IL-8 secretion of airway epithelial cells21. Thus, vesicle-mediated delivery of various cargo to host cells seem to be an important mechanism of host-pathogen communication and may play a major part in microbial pathogenesis.…”
mentioning
confidence: 99%
“…However, because virulence activation can be an asset one minute and a liability the next, information processing must be constant and fluid in response to the various physiologic contexts encountered in both space and time. During critical illness, as the microbiome collapses in both bacterial biomass and functional output, pathogen communities proliferate and develop stable strategies to co-exist by distancing themselves from immune clearance mechanisms (i.e biofilm production) or by directly disarming immune cells (74). During critical illness however, the presumption has always been that absent gross signs of inflammation or dysfunction in a particular organ where such pathobiomes might exist (i.e gut, lung), immune function and inflammation have little to do with these invisible microorganisms.…”
Section: Collapse Of the Intestinal Microbiome Emergence Of A Pathobmentioning
confidence: 99%
“…91,92 Recently, we and other colleagues found that msRNAs in OMVs of pathogenic bacteria can be delivered into host cells and thereby modulate host immune responses. 93,94 msRNA in P. aeruginosa reduced interleukin-8 (IL-8)…”
Section: Evs and Small Rna Secretionmentioning
confidence: 99%